Cosmic FPA calculator for mobile application development cost based on Unity3D game engine / Nur Atiqah Sia Abdullah and Nur Ida Aniza Rusli - Abdullah, Nur Atiqah Sia; Aniza Rusli, Nur Ida (Penerbit UiTM, 2014)
The emergence technology and popularity of mobile game application has led to higher demands in producing more colorful game environment, interactive design and selecting targeted platforms.To fulfil these requirements, mobile game engine; a framework to create mobile game application should provide greater complexity and parameters to be added in the mobile game properties.Thus, the effort costing of mobile application development is difficult to be estimated accurately. Therefore, this mobile game requirement is a new software concept that still needs to be tested properly to match the existing estimation models as these models are invented before the emergence of mobile application requirements. Hence, the motivation is to adapt COSMIC Functional Size Measurement (COSMIC FSM) for sizing the mobile game application development as it is one of the estimation models suitable to sizing embedded software and real-time system. This research uses Unity3D game engine as the platform to represent the mobile game requirements. These requirements are illustrated in the form of component diagrams and class diagrams in order to order to maintain and control the behavior of Unity3D features. The functional processes from component diagrams and class diagrams are captured to be used later in the sizing process using COSMIC FSM from the mapping between UML based-COSMIC FSM rules and measurement. A tool, COSMIC FPA Calculator for Mobile Application is developed to demonstrate the COSMIC FSM counting process for mobile game application costing.